The use of Moringa Oleifera Seed Powder as Coagulant to Improve the Quality of Wastewater and Ground Water. Issue 1 (January 2016) - Hendrawati,; Yuliastri, Indra Rani; Nurhasni,; Rohaeti, Eti; Effendi, Hefni; Darusman, Latifah K
Abstract: Wastewater and ground water treatment are mostly using Polyaluminum Chloride (PAC), a synthetic coagulant, which possess health risk and require expensive cost. This research was carried out to observe the effect of Moringa oleifera seed as natural coagulant to replace synthetic coagulant. M. oleifera reduced 98.6% turbidity of wastewater, 10.8% of its conductivity, 11.7% of its BOD and removed its metal contents (Cd, Cr, Mn). When applied to ground water, M. oleifera removed the turbidity of ground water as much as 97.5%, while reduced the conductivity and BOD of ground water 53.4% and 18%, respectively. The use of M. oleifera also reduced total number of coliform. The advantage of using M. oleifera is that it does not reduce pH as PAC, hence does not require further treatment to adjust pH of the treated water.